Microbiological sensors for the drinking water industry - Skovhus, Torben Lund; Højris, Bo (IWA Publishing, 2018)
"This most up-to date book addresses the interdisciplinary area of drinking water quality monitoring by microbiological sensors. It is edited and written by leading water professionals and experts, and binds together interests and competences within sensing technology, system behavior, business needs, legislation, education, data handling, and intelligent response algorithms"--Back cover